The miRNA-marker binding sites of breast cancer (Experimental biology, 2015)
1300 abstracts of articles devoted to search for miRNA markers for diagnostics of breast cancer were processed by miRCancer script. Search for binding sites of 357 miRNAs in mRNAs of 427 genes which proteins participate in breast cancer. The miRNA binding sites in 5’UTR, CDS, 3’UTR of mRNAs with free hybridization energy equaled greater than 90% were selected using MirTarget program. It was revealed, that miR-4417 and miR-665 are more prospect markers for prediction of breast cancer
Keywords: mRNA; miRNA; breast cancer; marker; miR-665; miR-4417.